An ecocriticism analysis of human-nature relationship in the film Jungle Cruise (2021) - Tiara Yessy Puspita; Singgih Daru Kuncara (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This research mainly focused on the representation of nature and the human-nature relationship in the film Jungle Cruise (2021), which was directed by Jaume Collet-Serra through the characters that involved with nature around them by using ecocriticism theory by Glotfelty and Garrard. The researcher used qualitative research in the form of explanations and descriptions. This film focused on the journey of Frank, Lily, and McGregor in the Amazon to find the legendary tree “The Tears of the Moon”. The data used in this research were the dialogues and actions of the characters that represented the ecocriticism. The data were collected by repeatedly watching the Jungle Cruise, focusing on the dialogue, scenes, and highlighting the events that indicated. This research used an ecocriticism approach to identify the representation of nature and the human-nature relationship. The analysis of this data showed Jungle Cruise film represents nature through wilderness, dwelling, and animals, and the human-nature relationship through the coexistence, provision, and nature exploitation.